Penerapan Sistem Penjualan Berbasis Web dengan Metode Waterfall pada Toko Murah Meriah Fashion Ponorogo - Pratama, Bayu Rizki Pratama; Maya Utami Dewi; Migunani Migunani; Arsito Ari Kuncoro; Khoirur Rozikin (Jurnal Manajemen Informatika & Teknologi, 2025)
This study aims to develop a web-based sales system for Toko Murah Meriah Fashion in Ponorogo City to address issues related to transaction recording, stock management, and product sales, which were previously handled manually. These issues led to inefficient sales processes and a high risk of data errors. To overcome these problems, the Waterfall software development method was applied, consisting of the stages of requirements analysis, design, implementation, testing, and maintenance. Data collection techniques included observation, interviews, and literature study. The system was developed using XAMPP as a local server, CodeIgniter 3 as the PHP framework, MySQL as the database, and Bootstrap to support a responsive user interface. Based on the results of analysis and testing using the black-box method, the system was successfully implemented and capable of performing all its functions effectively, including managing product data, orders, payments, and customer transaction history. With the implementation of this system, the sales process becomes more structured, faster, and efficient.